DETERMINING THE ASSOCIATIONS BETWEEN CROP PHENOLOGY, GROWTH, YIELD, AND YIELD-RELATED PARAMETERS OF MALT BARLEY (HORDEUM VULGARE) - ELSABET BAYISA; MESERET EJETA; KARTA KASKE; ASTAWUS ESATU; MEGERSA BAYISA; HASSEN SEID (Innovare Journal of Agricultural Sciences, 2024)
The study was conducted at two locations, namely Holeta and Kulumsa Agricultural research centers of Ethiopia, for 2 consecutive years from 2019 to 2021 main cropping seasons. The objective of the experiment was to determine the association between crop phenology, growth, yield, and yield-related parameters. One variety of newly harvested pre-basic seed class of malt barley variety, namely IBON 174/03, was used for the experiment. Total number of treatment combinations was eighteen. The treatments were laid out in a randomized complete block design in two factorial arrangements with three replications. The factors are five deterioration/aging days 0 (control/un-aged), 2, 4, 6, 8, and 10 days and three seeding rates (75, 100, and 125 kg/ha). Before artificial deterioration, the seed moisture content for all treatments was 12.5%. Seeds were subjected to artificial deterioration treatments and placed in an incubator at 42°C for 0 (control), 2, 4, 6, 8, and 10 days at approximately 100% relative humidity. The result revealed that above-ground dry biomass (AGDBM) and grain yield (GYLD) per hectare were significantly affected both by deterioration days and seed rate. As deterioration day increased the mean value for AGDBM and GYLD per hectare was significantly reduced and as the seeding rate increased from 75 to 125 kg/ha AGDBM and GYLD per hectare increased by 30.53% and 21.01%, respectively. The main effect of deterioration days showed a significant difference (p<0.05) for spike length (SL) as deterioration days increased from 2 to 10 days SL was reduced by 7.7–22.62% as compared to un-aged treatment but, the percentage reduction for barley seed deteriorated for 6 and 10 days recorded similar value which is 22.62% as compared to un-aged treatment. Seed per spike and thousand kernels weight were influenced by the main effect of seed rate but, not by deterioration days. As the seeding rate increased from 75 to 125 kg/ha, number of seeds per spike reduced by 4.75% whereas, seeds sown at a low seeding rate (75 kg/ha) recorded a higher thousand kernel weight (TKW) as compared to the seed sown at higher seed rate 100 and 125 kg/ha. Interaction effect of deterioration days and seed rate were only significant for TKW and it was non-significant for the rest of the evaluated crop phenology, growth, yield, and yield-related parameters. This study was only a field experiment result based on further conclusions on how aging can affect the genetic potential such as germination and viability; laboratory inclusive test will be required.